2016
DOI: 10.1007/s11751-016-0271-5
|View full text |Cite
|
Sign up to set email alerts
|

Subjective ulnar nerve dysfunction commonly following open reduction, internal fixation (ORIF) of distal humeral fractures and in situ decompression of the ulnar nerve

Abstract: The aim of this retrospective study was to investigate the frequency of persistent ulnar affection in patients who underwent open reduction and internal fixation (ORIF) of distal humeral fractures without ulnar nerve transposition or mobilisation. Eighty-two patients (53 women), mean age 62 years, were, at a mean of 48 months, reviewed through medical records and a subjective evaluation form concerning ulnar nerve problems. Ulnar nerve affliction, in most cases regarded as mild, was experienced by 22 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…It seems that anterior transposition of the nerve does not decrease the development of ulnar neuropathy after ORIF. 23,26,29,30 Shin et al found a 22% rate of postoperative ulnar nerve palsies despite performing adequate release and nerve transposition in most patients. When the nerve impinged upon the medial plate during elbow motion, irritation and transient sensory changes were noted.…”
Section: Ulnar Neuropathymentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that anterior transposition of the nerve does not decrease the development of ulnar neuropathy after ORIF. 23,26,29,30 Shin et al found a 22% rate of postoperative ulnar nerve palsies despite performing adequate release and nerve transposition in most patients. When the nerve impinged upon the medial plate during elbow motion, irritation and transient sensory changes were noted.…”
Section: Ulnar Neuropathymentioning
confidence: 99%
“…Ulnar nerve affliction, in most cases regarded as mild, was experienced by 22 patients (27%) and was significantly associated with multiple surgeries. 30…”
Section: Ulnar Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Dual plate fixation has been proven most beneficial and the parallel concept biomechanically preferable even though not clearly demonstrated in clinical practice [5][6][7][8][9][10][11][12][13][14][15][16]. Fracture surgery of the distal humerus requires exposure of the fracture, usually by moving the triceps out of the way at the same time protecting the ulnar nerve, and several different methods have been described [17][18][19][20]. The predominating approach, especially for AO/OTA type C fractures, appears to be the olecranon osteotomy, another approach less investigated is the triceps split [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The reported postoperative incidence of ulnar nerve affection varies widely between 0 and 51% (Holdsworth and Mossad 1990, Sodergard et al 1992, Wang et al 1994, Kundel et al 1996, Gupta and Khanchandani 2002, Soon et al 2004, Shin and Ring 2007, Wiggers et al 2012). Svernlov et al found that 27% of patients had ulnar nerve affection after 48 months, but interestingly this was regardless of whether the medial column was involved in the fracture and secured with a plate and screws or not (Svernlov et al 2017). Vasques et al came to the conclusion that it may be the trauma itself that causes ulnar nerve dysfunction, though it should be mentioned that the main dysfunction is sensory, and motoric dysfunction is rare (Vazquez et al 2010).…”
Section: Ulnar Nerve Affectionmentioning
confidence: 99%